If Indonesia is Too Hard to Understand, Let's Start with Bali - Graeme MacRae (Journal of Indonesian Social Sciences and Humanities, 2010)
Stereotypical representations, especially those by the media, are for most outside observers, the means and an obstacle to understanding Indonesia. One way around such stereotypes is to look at the way Indonesians themselves understand Indonesia. This essay reports and re?ects on Balinese understandings of Indonesia in the wake of the political, economic and terrorist upheavals of the early years of the twenty-first century. It concludes with an epilogue and update, arguing that the real issues for understanding Indonesia are now environmental.